Thermal lesion of renal tumour as a function of catheter material property (2018)
The extent of lesion achieved during microwave ablation is dependent on some factors which include the time period of application, its intensity, antenna geometry, and relative permittivity of the tissue. Several studies have been conducted on microwave ablation for the treatment of tumours and have focused on different antenna geometries, its intensity, and time of application. This work seeks to find a correlation between the relative permittivity of the catheter and the temperature distribution which determines necrosis of the tissue by using Tefzel ETFE, Teflon FEP, PFA Teflon type A, PFA Teflon type B, Teflon AF, and PTFE Teflon type B while modelling using COMSOL Multiphysics. The extent of the thermal lesion was observed to be dependent on the relative permittivity of the catheter material, with Tefzel ETFE giving the best performance and Teflon AF providing the least.